Removal Study of Crystal Violet and Methylene Blue From Aqueous Solution by Activated Carbon Embedded Zero-Valent Iron: Effect of Reduction Methods - Wang, Yongmei; Chen, Tiantian; Zhang, Xiaolin; Mwamulima, Teza (Frontiers in Environmental Science, 2021)
Zero valent iron (ZVI) particles were embedded into porous materials for avoiding their aggregation and separation problems in the controlled synthesis process. To investigate the adsorption mechanism of crystal violet and methylene blue, activated carbon (AC) and AC based ZVI extracted by solid phase and liquid phase reduced approaches were conducted. Characterization methods of specific surface area, scanning electron microscopy (SEM) and X-ray diffractograms (XRD) were used to elucidated the structure of adsorbents, and the adsorption capacities of crystal violet and methylene blue were obtained under the experiment conditions of various pH values (2.0-10.0), adsorption time (0-72 h) and temperatures (30-50 oC). The adsorption of crystal violet/ methylene blue was controlled by both chemisorption and reduction. The adsorption processes were fitted to pseudo-second-order kinetic model, and that of reduction kinetics were suitable to pseudo-first-order kinetic model. The thermodynamic study revealed that the adsorption of crystal violet and methylene blue was endothermic and spontaneous, and the adsorption isotherms were fitted well to Langmuir model. Different adsorption capacities of crystal violet and methylene blue on various adsorbents were found, indicating that both the properties of adsorbents (pore size, specific surface area and chemical functional groups) and the structures of adsorbates had significant effect on the removal of dye molecules.